Integrated in silico – in vitro strategy for the discovery of potential xanthine oxidase inhibitors from Egyptian propolis and their synergistic effect with allopurinol and febuxostat. Issue 5 (21st January 2022) - Ghallab, Dina S.; Shawky, Eman; Metwally, Ali M.; Celik, Ismail; Ibrahim, Reham S.; Mohyeldin, Mohamed M.
Abstract : Xanthine oxidase (XO) has been well-recognized as a validated target for the treatment of hyperuricemia and gout. Abstract : Xanthine oxidase (XO) has been well-recognized as a validated target for the treatment of hyperuricemia and gout. Currently, there are two drugs in clinical use that shut down XO overactivity, allopurinol and febuxostat; however, detrimental side effects restrict their applications. Propolis is a unique natural adhesive biomass of structurally variable and biologically active metabolites that exert remarkable health benefits. Moreover, combination drug therapy has become a promising pharmacotherapeutic strategy directed for reformulating existing drugs into new combination entities with potentiating therapeutic impacts. In this study, computer-aided molecular docking and MD simulations accompanied by biochemical testing were used for mining novel pharmacologically active chemical entities from Egyptian propolis to combat hyperuricemia. Further, with a view to decrease the potential toxicity of synthetic drugs and enhance efficacy, propolis hits were subjected to combination analysis with each of allopurinol and febuxostat. More specifically, Glide docking was utilized for a structure-based virtual screening of in-house datasets comprising various Egyptian propolis metabolites. Rosmarinic acid, luteolin, techtochrysin and isoferulic acid were the most promising virtual hits. In vitro XO inhibitory assays demonstrated the ability of these hits to significantly inhibit XO in a dose-dependent manner. Molecular docking and MD simulations revealed a cooperative binding mode between the discovered hits and standard XO inhibitors within the active site. Subsequently, the most promising hits were tested in a fixed-ratio combination setting with allopurinol and febuxostat separately to assess their combined effects on XO catalytic inhibition. The binary combination of each techtochrysin and rosmarinic acid with febuxostat displayed maximal synergy at lower effect levels. In contrast, individually, techtochrysin and rosmarinic acid with allopurinol cooperated synergistically at high dose levels. Taken together, the suggested strategy seems imperative to ensure a steady supply of new therapeutic options sourced from Egyptian propolis to regress the development of hyperuricemia.